Asesmen terhadap Partisipasi Masyarakat dalam Perencanaan Kolaboratif Pedesaan: Kasus Dusun Trucuk, Kabupaten Bantul, Indonesia - Depari, Catharina (Sodality: Jurnal Sosiologi Pedesaan, 2023)
To address poverty, many rural communities mobilized tourism at the grassroots level in Indonesia. Such manners raised the government’s concern about potential social-environmental problems, motivating them to collaborate with academia to develop responsible tourism through placemaking. Meanwhile, studies evaluating the success/failures of placemaking in the rural context remain limited. This article aims at qualitatively assessing the capacity of rural placemaking to motivate community participation by using the Trucuk sub-village in Bantul Regency as the case study. Methods employed are semi-structured interviews, observations, and document reviews. Using the theories of Arnstein, Innes and Booher, and Project for Public Space as its framework, this study found that the lack of community participation from the ground rules establishment and negotiations of power redistribution, awareness development of making use of local capital to affect outcomes, and diverse opinions in planning led to declining interest of the community in participating. Future planning should address those issues by ensuring the involvement of diverse groups within the community, employing innovative and interactive methods to foster participation, evaluating the representativeness of the tourism awareness group, and setting a considerable limit on the authority’s dominance in the planning.